Pengaruh Influencer, Follower Instagram dan Youtuber Dalam Jual Beli Baju Bekas Branded - Misi Anggraini; Rozalinda (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2022)
Based on the dilemma that will be examined, here the author examines the news how many effects should be related to buying and selling transactions of branded used clothes according to followers from Instagram, Influencers and Youtubers. In this study, the method is for field research or qualitative in the field research approach, data analysis on phenomenology by examining what happened and related to the law in buying and selling transactions in Islam. Apart from that, various data sources are library materials by reviewing books, journals, previous researchers related to the material under study. The sample population of consumers of branded used clothes is at least 100 respondents or less. The data collection technique uses a survey using digital assistance, namely Google Form. The results of the study provide that the influencer's role has a huge impact on followers based on what they post and tell through social media such as Instagram. Due to this impact, with the presence of Influencers, Instagram followers/followers and also Youtubers, the buying and selling of branded used clothes has increased and is in great demand among young people, especially in terms of fashion, dominant expression, social media influence, environment and original product quality.